Biodiesel industrial waste based on Jatropha curcas as a fungicide to control Fusarium oxysporum and Alternaria solani - Sukorini, Henik; Widyastuti, Dyah Erni; Kurniawati, Dini; Suwannarat, Sawita; Mel, Maizirwan; Hendroko Setyobudi, Roy (EDP Sciences, 2023)
Fusarium oxysporum (Schlecht. emend. Snyder & Hansen.) is the most devastating pathogens causing wilt disease on the tomatoes (Solanum lycopersicum L.) plant, whereas Alternaria solani (Sorauer), is a pathogen that caused early blight on potatoes (Solanum tuberosum L.) Jatropha curcas L. is a biodiesel material known as a potential fungicide. The industrial biodiesel waste based on J. curcas was not yet observed, particularly on the utilization of waste mainly for green manure and biogas. This research aimed to evaluate the extract of industrial biodiesel waste based on J. curcas against F. oxysporum and A. solani. There were 2 × 103 mg L-1 , 4 × 103 mg L-1 , 6 × 103 mg L-1 , 8 × 103 mg L-1 , and 10 × 103 mg L-1 of crude extract that were tested on both pathogens in vitro and in vivo. The concentration of the extract was in an effective range of 10 × 103 mg L-1 and was able to inhibit the growth of all isolates of F. oxysporum from both locations by more than 80 %, but the inhibition of the pathogen A. solani was less than 76 %.